2006
DOI: 10.1021/ja058282w
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt Particle Size Effects in the Fischer−Tropsch Reaction Studied with Carbon Nanofiber Supported Catalysts

Abstract: The influence of cobalt particle size in the range of 2.6-27 nm on the performance in Fischer-Tropsch synthesis has been investigated for the first time using well-defined catalysts based on an inert carbon nanofibers support material. X-ray absorption spectroscopy revealed that cobalt was metallic, even for small particle sizes, after the in situ reduction treatment, which is a prerequisite for catalytic operation and is difficult to achieve using traditional oxidic supports. The turnover frequency (TOF) for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

71
1,109
10
15

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,392 publications
(1,205 citation statements)
references
References 66 publications
(116 reference statements)
71
1,109
10
15
Order By: Relevance
“…16 Furthermore, Au nanoparticles showed a remarkably high activity for CO oxidation below 5 nm particle diameter, reaching a maximum in activity at 2-3 nm size. 17 Ruthenium has interesting catalytic properties for CO oxidation if prepared in the form of nanoparticles of diameter between 2 nm and 6 nm.…”
Section: Introductionmentioning
confidence: 98%
“…16 Furthermore, Au nanoparticles showed a remarkably high activity for CO oxidation below 5 nm particle diameter, reaching a maximum in activity at 2-3 nm size. 17 Ruthenium has interesting catalytic properties for CO oxidation if prepared in the form of nanoparticles of diameter between 2 nm and 6 nm.…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the increase in demand for transportation fuels and the large reserves of natural gas have made FTS an attractive industrial process. In the FTS process, cobaltbased catalysts, owing to low water-gas shift activity and remarkable stability, is considered to be the favorable catalyst for the synthesis of long-chain hydrocarbons from synthesis gas with a H 2 /CO ratio about 2 [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated how site time yield decreases dramatically for very small cobalt particles, i.e. below a cobalt particle size of 6-8 nm 27 , which defines an optimum on how efficiently cobalt can be used. Readers who are interested in more information on preparation and characteristics of cobalt catalysts are referred to the review by Khodakov et al 11 .…”
Section: Cobalt Catalystsmentioning
confidence: 99%
“…In contrast to the effect on Co catalysts, alkali is known to promote desirable effects in iron catalysts and potassium is commonly added as a promotor 27,33 . A recent study have also shown that in operando addition of 400 ppbw KCl and NaCl, and also 40 ppmw NaHCO3 and KHCO3 with the synthesis gas, did not have any measureable impact on catalytic activity on a precipitated iron catalyst after 400 hours of operation 77 .…”
Section: Alkali and Alkaline Earth Elements On Co And Fementioning
confidence: 99%